GIS tool to assist the management, display and archiving of water catchment areas and their diffuse pollution pressures. - Yahya, Madi-Kimba (Cranfield University, 2006)
This project aims to develop an application to illustrate the extent at which relational database management can be used to improve catchment area management within the Environment Agency through the application of Geographic Information Systems (GIS). The goal is to advance fundamental understanding of the spatial dimensions of these databases, their interrelationships and how they can aid decision making. The Environment Agency (EA) has possession of a lot of GIS data that is not fully utilized and this project is a first step in the right direction to getting more users within the EA to make full use of the data available within their organization to aid them make informed strategic and tactical decisions. This was done by developing a Graphical User Interface (GUI) that is user friendly and helps access the database quickly and easily. A toolbar was also developed to host command buttons that have been customized to make the use of ArcMap easier. The user will be able to execute functions without the need of extensive background knowledge of ArcGIS and the intricacies associated with each individual function. Ordnance Survey MasterMap data is also used (to a limited extent due to time constraints) to illustrate the scenarios faced and the decision processes that will need to be followed. This example will show how the relationship between Hazard assessment and risk mitigation within catchments can be linked through a GIS system.
Keywords: Informed strategic decisions; informed tactical decisions; database; map data; catchment area management; spatial dimensions of databases